2017
DOI: 10.1080/15376516.2017.1368054
|View full text |Cite|
|
Sign up to set email alerts
|

The mechanism of protective effect of crocin against liver mitochondrial toxicity caused by arsenic III

Abstract: In this study, we want to understand whether crocin could prevent mitochondrial damage caused by As III. For this purpose, we determined different mitochondrial toxicity endpoints caused by As III. We evaluated mitochondrial ROS formation, lipid peroxidation, mitochondrial membrane potential (MMP) collapse, mitochondrial outer membrane integrity and cytochrome c release. Our results showed that pretreatment with crocin at a concentration of 25 µg/ml significantly (p < 0.001) reduced As III-induced mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…CS contains various secondary metabolites that are responsible for different pharmacological activities. Traditionally CS has been used for various ailments like antihypertensive [10], neuroprotective [11], antitussive [12], aphrodisiac [13], antioxidant [14], antinociceptive [15], anti-inflammatory [16] activities.…”
Section: Introductionmentioning
confidence: 99%
“…CS contains various secondary metabolites that are responsible for different pharmacological activities. Traditionally CS has been used for various ailments like antihypertensive [10], neuroprotective [11], antitussive [12], aphrodisiac [13], antioxidant [14], antinociceptive [15], anti-inflammatory [16] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Pourahmad J et, al. revealed that the hepatotoxicity caused by diclofenac is associated with oxidative stress [13]. On the other hand, liver toxicity decreases with antioxidant compounds, which is another indication of the effect of oxidative stress and free radicals on liver toxicity [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, crocin is among the major active components of saffron and is a pharmacologically active and water‐soluble carotenoid isolated from saffron crocus ( Crocus sativus L .). There are plenty of studies that have exhibited that crocin possesses therapeutic and pharmaceutical properties, including high antioxidant, anti‐inflammatory, and neuroprotective activities either in vivo or in vitro . Therefore, crocin, by acting as an antioxidant or radical scavenger, could protect cells and tissues against oxidative stress damages .…”
Section: Introductionmentioning
confidence: 99%
“…There are plenty of studies that have exhibited that crocin possesses therapeutic and pharmaceutical properties, including high antioxidant, anti-inflammatory, and neuroprotective activities either in vivo or in vitro. [21][22][23][24][25] Therefore, crocin, by acting as an antioxidant or radical scavenger, could protect cells and tissues against oxidative stress damages. [1] Given the…”
Section: Introductionmentioning
confidence: 99%